TECHNIQUES IN PRESENTING VOCABULARY TO YOUNG EFL LEARNERS - Annisa Awaluddin (Journal of English and Education, 2013)
This paper reports on research results aimed at investigating the techniques used by a teacher of a young learner course in presenting meaning and form of vocabulary, as well as the reasons in employing the techniques. This study applied framework from Takač (2008). Observations and interview were carried out to collect the data. The findings indicate that the teacher applied various techniques with various reasons, both in presenting word meaning and form. In presenting word meaning, the teacher mostly employed Real Objects which comprised the use of pictures, realia, and demonstration. In presenting word form, the teacher mostly employed Graphic Form. Keywords:Teaching techniques, vocabulary, presenting vocabulary, young learners